2020
DOI: 10.1111/codi.15377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liposomal bupivacaine on opioid requirements and length of stay in colorectal enhanced recovery pathways: A systematic review and network meta‐analysis

Abstract: Aim: Reducing postoperative opioid consumption is a key aim of enhanced recovery after colorectal surgery protocols. Potential solutions include anaesthetic techniques such as local infiltration of anaesthetic agents or transversus abdominis plane (TAP) blocks. This study aimed to assess the efficacy of liposomal bupivacaine (LB) for colorectal resections, across a variety of anaesthetic techniques. Methods: PubMed, Scopus and Embase databases were searched for relevant studies assessing LB, administered by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…Two studies compared liposomal bupivacaine to saline injection or no injection at all and found no difference in pain scores on postoperative days 1–4 [ 30 , 32 ]. Chen et al also found no difference in pain scores on postoperative days 1–4 when comparing supraclavicular nerve block with and without the addition of liposomal bupivacaine [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies compared liposomal bupivacaine to saline injection or no injection at all and found no difference in pain scores on postoperative days 1–4 [ 30 , 32 ]. Chen et al also found no difference in pain scores on postoperative days 1–4 when comparing supraclavicular nerve block with and without the addition of liposomal bupivacaine [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these studies on the use of liposomal bupivacaine in total knee arthroplasty, there is also an abundance of data, including meta-analyses and systematic reviews, on the use of liposomal bupivacaine in total hip arthroplasty and total shoulder arthroplasty [ 27 31 ]. Some of these studies, as well as many studies in the general surgery, and anesthesia literature fail to identify much, if any, difference between the use of standard bupivacaine and liposomal bupivacaine [ 32 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…195 Data remain controversial regarding the purported extended duration of benefit with long-acting local anesthetics such as liposomal bupivacaine in reducing postoperative opioid consumption. 196–199…”
Section: Perioperative Interventionsmentioning
confidence: 99%
“…195 Data remain controversial regarding the purported extended duration of benefit with long-acting local anesthetics such as liposomal bupivacaine in reducing postoperative opioid consumption. [196][197][198][199] Another option, spinal analgesia with intrathecal morphine administration, can be used in the perioperative setting. Studies and meta-analyses have shown that intrathecal morphine is more effective than intravenous opioids in laparoscopic surgery and is associated with lower pain scores.…”
Section: Standardized Order Sets Should Be Used In Enhanced Recovery ...mentioning
confidence: 99%
“…Additionally, there is evidence to support the use of LB in abdominal surgery when given as a transversus abdominis plane block 13–15. Specific to colorectal resections, but not discriminatory in the mode of its delivery, two systematic reviews with meta-analysis associate the use of LB with reduced postoperative morphine requirements and shorter lengths of stay 16 17. To our knowledge, there are no studies that directly compare the efficacy of LB to bupivacaine delivered via RSCs.…”
Section: Introductionmentioning
confidence: 99%